The Unexpected Orthodoxy of Donald J. Trump: White Evangelical Support for the 45th President of the United States. (20th December 2018) - Martí, Gerardo
Abstract: By now, most political observers have absorbed the pervasiveness of white Evangelical support for Donald J. Trump not only in the 2016 presidential election results but also in the poll numbers showing continued approval since then. Nevertheless, many social scientists—even those who are Evangelical themselves—remain puzzled regarding Evangelical enthusiasm for Trump, a man who has frequently demonstrated seemingly "un-Christian" speech and behavior. Drawing on Brophy's outstanding analysis of orthodoxy as project and the notion that behavioral standards are both variable and subordinate to the defense of orthodox identity, Trump can be understood as fully orthodox within an Evangelical framework insofar as he occupies a pivotal role in forcefully affirming their feeling of being threatened and working to maintain their interests into the future. Thus, despite Trump's apparently non-Christian actions, his public support and political enactment of Evangelical priorities through federal appointments and policies reveal him to be unexpectedly orthodox after all.